Radio frequency identification technology (RFID) in internal industrial logistics: exploratory research at a machining company for the aerospace sector - Alberto Marques, Carlos; Furlan Jr., Valdir; Muniz, Jorge; Alberto Chaves, Carlos; Urias, Ângelo (Revista Gestão da Produção Operações e Sistemas, 2009)
Applications related to materials management are disseminating Radio-Frequency Identification (RFID) technology around the world. The scope of this technology enables managers to control several business processes and solutions for daily traceability. This article explores RFID applications in internal machining environment logistics where the use of barcode labels does not meet all the detection, identification and traceability needs. This study is classified as exploratory and was conducted in 2007, at a machined components industry for the aerospace sector. This study analyzes the deployment and use of this technology. Hopefully, the learning process that results from this study will disseminate experiences and practices in the use of RFID. Keywords: RFID; materials management; traceability; internal logistic.